Phytochemicals From Vicia faba Beans as Ligands of the Aryl Hydrocarbon Receptor to Regulate Autoimmune Diseases - Méndez-López, Luis Fernando; Sosa de León, Deisy; López-Cabanillas Lomelí, Manuel; González-Martínez, Blanca Edelia; Vázquez-Rodríguez, Jesús Alberto (Frontiers in Nutrition, 2022)
Autoimmune diseases are characterized by the aberrant production of self-reactive antibodies and T cells. Increasing evidence supports those dietary factors impact the immune balance at the interface of the gastric mucosa and the gut microbiota. The aryl receptor plays a protective role against autoimmune diseases via the transduction of pathways that restore the balance among T helper 17 cells, T regulatory cells, intestinal intraepithelial lymphocytes, and mucosal homeostasis. Legumes are associated with gut health benefits, and increasing evidence indicates that their consumption reduces the risk of chronic diseases, including autoimmunity. Recent metabolomic approaches enabled the comprehensive characterization of the phytochemical composition of broad bean (Vicia faba L.). The bioactive compounds founded include alkaloids, terpenoids, jasmonates, and polyphenols; however, they know just a few of the mechanisms responsible for their health-promoting properties. This article aims to review the metabolic fate and the potential ligand aryl receptor activity (AhR) of the most abundant antioxidants present in broad bean and used metabolomic prediction and molecular docking techniques. All the compounds analyzed present binding energy <-5 kcal/mol for AhR, and the compounds reported are consistent with the literature. Therefore, the chronic consumption of phytochemicals in Vicia faba L., and their metabolites produced by endogenous via or microbiota, may protect against the autoimmune disease's pathogenesis by AhR modulation.